Ketamine in Pain Management - Persson, Jan (CNS Neurosci Ther, 2013)
For ketamine's fiftieth birthday, a narrative review of this unique drug in pain management is presented. Its history is traced from its conception, and its heritage, as a phencyclidine offspring, delineated. The earliest roots of the conceptions concerning the mechanisms of action are sought, and then followed in preclinical as well as clinical research. The major proposed mechanisms in the literature are commented on and evaluated. The growth of the clinical evidence for perioperative pain, acute pain, and chronic pain is followed from early attempts to systematic reviews. Finally, an attempt is made to foresee what the next 50 years might hold in store for our 50 years old.